Health Literacy and Osteoarthritis Self-Management - Ray, Marks (Journal of Aging Research And Healthcare, 2018)
Background: Osteoarthritis is a disabling joint disease with no known cure that negatively effects life quality among high numbers of aging adults. Aim: To examine the concept of health literacy as a potentially overlooked, but highly salient, disease correlate among this older chronically disabled group. Method: A literature search using the key terms osteoarthritis and health literacy was conducted using the major data bases. Results: Although almost no work has focused on health literacy and osteoarthritis, the concept of health literacy is clearly linked to health status and health outcomes. Varying from marginal to high, health literacy is not always assessed or recognized as being clinically relevant, however, despite a large volume of related literature. Conclusion: Acknowledging the possible role of limited health literacy in the context of osteoarthritis disease progression, and applying carefully tailored directives for overcoming any related health literacy limitations may offer a novel approach for improving the outcomes for older people with this condition.
Keywords: Health literacy; Older adults; Osteoarthritis; Prevention; Rehabilitation